Iranian Nuclear and United States Interests in the Middle East, 2005-2013: an analysis of neorealism - Rahman, Riki; S. Hazis, Faisal; Ramli, Rashila (College Of International Affairs, Tamkang University, 2010)
Iran’s Ahmadinejad decided to reactivate the development of nuclear technology programs. This led the United States to claim that Iran was trying to create nuclear weapons and pressured Iran to terminate it. The purpose of this article is to identify the US strategic interests in the Middle Eastern region in relation to Iran's nuclear. It is then elaborated in detail and analysed using a neorealism perspective. This article is qualitative in which primary data is collected through interviews with field experts. In addition, reports and content analysis are also part of the primary data of this article, while secondary data refers to authoritative internet materials. We argue that US strategic interests in the Middle East in the context of Iran's nuclear is to control Persian Gulf oil resources, preventing wider Iran's influence in the Middle East, providing military protection to the Persian Gulf states as the largest oil producers in the Middle East and protecting Israel whom is a close US ally. When viewed from neorealism perspective, we argue that Iran's action under Ahmadinejad to continue its nuclear program is justified as it is a survival effort and to prevent external threats, though this will lead to nuclear competition in the region.